Método autotutorial de ensino de física básica através do uso de microcomputadores como meio auxiliar de ensino - Nardi, Roberto; Juraitis, Klemensas Rimgaudas (Semina: Ciências Exatas e Tecnológicas, 2004)
<!–[if gte mso 9]> Normal 0 21 false false false MicrosoftInternetExplorer4 <![endif]–><!–[if gte mso 9]> <![endif]–> <!– /* Font Definitions */ @font-face font-family:Verdana; panose-1:2 11 6 4 3 5 4 4 2 4; mso-font-charset:0; mso-generic-font-family:swiss; mso-font-pitch:variable; mso-font-signature:536871559 0 0 0 415 0; /* Style Definitions */ p.MsoNormal, li.MsoNormal, div.MsoNormal mso-style-parent:""; margin:0cm; margin-bottom:.0001pt; mso-pagination:widow-orphan; font-size:12.0pt; font-family:"Times New Roman"; mso-fareast-font-family:"Times New Roman"; @page Section1 size:612.0pt 792.0pt; margin:70.85pt 3.0cm 70.85pt 3.0cm; mso-header-margin:36.0pt; mso-footer-margin:36.0pt; mso-paper-source:0; div.Section1 page:Section1; –> <!–[if gte mso 10]> <![endif]–> We describe in this paper, an experiment to be carried out in the Departament of Physics, Universidade Estadual de Londrina. In this experiment, a self-tutorial method, where the use of microcomputers as an auxiliary aid is employed for the teaching of Basic Physics. Methodology, underlying of the basic phylosophy the method, and the programming techniques to be used, are here discussed.